Climate Change‐Driven Heatwaves Pose Lethal Risks to Newborn Forest Bats - Danilo Russo; Anne Mäenurm; Luca Cistrone; Adriano Martinoli; Greta Foiani; Valentina Giongo; Stefania Leopardi (Ecology and Evolution)
ABSTRACT Climate change poses a significant threat to biodiversity, with extreme weather events such as heatwaves exacerbating the risks to animal populations. Temperature extremes can cause high physiological stress in animals, particularly in species or life stages with limited thermoregulatory abilities. While available evidence pertains to flying foxes and bats using bat boxes or dwelling in urban environments, heatwave‐induced mortality in forest‐dwelling species in temperate forests has not been reported. We present the first evidence of heatwave‐related mortality in temperate forest bats, specifically in common noctules Nyctalus noctula, observed in northeast Italy during the summers of 2023 and 2024. Our fieldwork, conducted in a forest fragment in the Friuli‐Venezia Giulia Region (Northeastern Italy), identified 17 dead juvenile bats found at the base of roost trees during periods of extreme heat (Tmax ≥ 30°C). Laboratory necropsies revealed that the cause of death was consistent with heat‐related stress, as no viral infections were detected, and recent feeding evidence was present in a few individuals. Dead bats are difficult to find in forests, especially when mortality occurs in unsurveyed areas, scavengers remove carcasses, or deaths go unnoticed within roost cavities. Consequently, our observations likely represent only a limited fraction of actual mortality. The phenomenon may be quantitatively significant and widespread. The findings highlight the vulnerability of bat populations to heatwaves, particularly in fragmented forest habitats where roosting opportunities are limited. Our results allow us to hypothesise that forest fragmentation increases exposure to heat stress, particularly along forest edges. In the context of climate change, roosts deemed suitable may act as ecological traps, making this a hypothesis worth testing.